Błędny rycerz, pielgrzym, tułacz, Rom – powroty do tematów nomadycznych w literaturze czeskiej - Gawarecka, Anna (Komisja Slawistyczna PAN, Oddział w Poznaniu, IFS UAM, Wydawnictwo PRO, 2017)
The topics of pilgrimage, wandering or roam which were the main subject of the romantic anthropological ideas often returns in Czech literature. On the one hand these topics are included into the resources of universal motifs of the Western European culture, on the other hand they represents an important strand in the contemporary discussion on the modern conditio humana. The repetition of the nomadic topics, based on the advanced chain of the intertextual connections and assumed the preliminary understanding with the reader, who is knowledgeable in a world of the prearranged meanings and ways of representations of the figure of wanderer/pilgrim/ vagrant, is an argument of the long lasting field of imagination which is connected with this figure. It i also an suitable tool for the research of the journey as a symbol of human life.
Keywords: pilgrimage; wandering; Gypsies; nomadism; romanticism